Indonesian coffee exports and its relation to global market integration - Fitriani Fitriani; Bustanul Arifin; Hanung Ismono (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Coffee price is an important indicator that stimulates farmers to advance their welfare. Unfortunately, coffee crisis makes the farm gate price uncertain and volatile. This study aims to explore the Indonesian coffee export situation related to price risks and coffee market integration between Indonesian coffee price and international price. The time series data were the coffee price from 1987 to 2014 in Indonesian domestic market and in global trade in London. Vector Error Correction Model (VECM) approach was applied to test market integration based on Ravallion’s equation. Based on the analysis, the results of the study revealed that Indonesian coffee export performed progressively in the last decade. Export destination countries for Indonesian coffee also developed broadly.  There was market integration on the Indonesian coffee market and global price in the London terminal.  Although not fully, the shock in the international price was somehow felt in the Indonesian coffee market.  There were sufficient shreds of evidence to conclude that the Indonesian coffee market is well integrated with the international market in the long run. The changing coffee price in Indonesia and the International market adjusted in the next three years.  In short term, Indonesian coffee price was 76% influenced by international price changes, but not vice versa.JEL Classification D49; Q02; Q17